A pediatric patient with bilateral tracheobronchial foreign body successfully treated using surgical intervention with extracorporeal circulation: case report and literature review - Li-Qiang Xu; Qiang Liu; Min Zeng; Hui-Zhi Yan; Nan Hu; Qun-Xian Zhang; Qiang Guo; Jia-Long Guo; Jun Zhang (Frontiers Media S.A., 2024)
Unilateral Tracheobronchial foreign body (TFB) present a common clinical disease, whereas bilateral TFB is a rare and acute condition associated with high mortality rates. This case study discusses a pediatric patient hospitalized due to respiratory distress following accidental ingestion of peanut kernels. A plain chest CT scan revealed obstructive emphysema in the right main bronchus and a foreign body at the opening of the left main bronchus. Surgical removal of the bilateral TFB under extracorporeal circulation resulted in a successful postoperative recovery, leading to discharge on the 9th day. A comprehensive literature search was conducted across databases including PubMed, Web of Science, EMBASE, Cochrane Library, and CNKI, spanning publications from January 2014 to October 2023, utilizing keywords "bronchial foreign body" and "Peanut". After deduplication and relevance screening, 9 pertinent literature sources were included. The objective of this study is to enhance clinical practitioners' understanding of TFB management and improve diagnostic and treatment capabilities through analysis of age of onset, clinical manifestations, diagnosis, and treatment approaches in critically ill pediatric patients.